Anti-Mycobacterium tuberculosis activity of fungus Phomopsis stipata - Prince, Karina Andrade de [UNESP]; Sordi, Renata [UNESP]; Pavan, Fernando Rogério [UNESP]; Santos, Adolfo Carlos Barreto [UNESP]; Araujo, Angela R. [UNESP]; Leite, Sergio R.A. [UNESP]; Leite, Clarice Queico Fujimura [UNESP] (Sociedade Brasileira de Microbiologia, 2012)
Our purpose was to determine the anti-Mycobacterium tuberculosis activity of the metabolites produced by the endophitic fungus Phomopsis stipata (Lib.) B. Sutton, (Diaporthaceae), cultivated in different media. The antimycobacterial activity was assessed through the Resazurin Microtiter Assay (REMA) and the cytotoxicity test performed on macrophage cell line. The extracts derived from fungi grown on Corn Medium and Potato Dextrose Broth presented the smallest values of Minimum Inhibitory Concentration (MIC) and low cytotoxicity, which implies a high selectivity index. This is the first report on the chemical composition and antitubercular activity of metabolites of P. stipata, as well as the influence of culture medium on these properties.
Keywords: Phomopsis stipata; antimycobacterial activity; Mycobacterium tuberculosis